Semantic and Lingua-Cultural Features of English and Uzbek Medical Periphrases - Kobilova Aziza Bakhriddinovna (Researchparks Publishing, 2022)
Periphrases are one of the most important stylistic devices associated with the speech process. Periphrases serve to enrich speech, make it attractive, figurative, and impressive, and enhance the level of language. In this article, investigating semantic and lingua-cultural aspects of the medical periphrases of the English and Uzbek languages, passages of journalistic texts were analyzed.